Fidelity of neural reactivation reveals competition between memories - Kuhl, Brice A. (National Academy of Sciences, 2011)
Remembering an event from the past is often complicated by the fact that our memories are cluttered with similar events. Though competition is a fundamental part of remembering, there is little evidence of how mnemonic competition is neurally represented. Here, we assessed whether competition between visual memories is captured in the relative degree to which target vs. competing memories are reactivated within the ventral occipitotemporal cortex (VOTC). To assess reactivation, we used multivoxel pattern analysis of fMRI data, quantifying the degree to which retrieval events elicited patterns of neural activity that matched those elicited during encoding. Consistent with recent evidence, we found that retrieval of visual memories was associated with robust VOTC reactivation and that the degree of reactivation scaled with behavioral expressions of target memory retrieval. Critically, competitive remembering was associated with more ambiguous patterns of VOTC reactivation, putatively reflecting simultaneous reactivation of target and competing memories. Indeed, the more weakly that target memories were reactivated, the more likely that competing memories were later remembered. Moreover, when VOTC reactivation indicated that conflict between target and competing memories was high, frontoparietal mechanisms were markedly engaged, revealing specific neural mechanisms that tracked competing mnemonic evidence. Together, these findings provide unique evidence that neural reactivation captures competition between individual memories, providing insight into how well target memories are retrieved in the present and how likely competing memories will be remembered in the future.